DNA Marker-assisted improvement of the staple crops in sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
These proceedings based on a workshop held by IITA in Nigeria in August 1996 have been published with CTAŽs support.IITA/CTA co-publication,edited by JH Crouch and A Tenkouano.1999.240 pp.ISBN 978 131 163 0.CTA number 960. 40 credit points.